2012
DOI: 10.4236/ojmm.2012.23007
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological Patterns of AIDS in a Reference Center from Catanduva, São Paulo State, Brazil

Abstract: Objective: Hereby we present the epidemiological and clinical profile of HIV-infected population before and during the highly active antiretroviral therapy (HAART) era from a tertiary care hospital in the Southeastern region of Brazil. Methods: A retrospective, cross-sectional and descriptive study was carried out, this involved the analysis of the medical records of patients diagnosed with HIV-1/AIDS admitted to Hospital Escola Emílio Carlos, located in the municipality of Catanduva, State of São Paulo, Brazi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
9
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(14 citation statements)
references
References 31 publications
5
9
0
Order By: Relevance
“…The present study revealed a higher incidence of HIV among young adult males, as previously described by our group at the municipality of Catanduva, São Paulo (2) . However, there was a decrease in the male: female (M:F) ratio among infected individuals in the ART era (1.89M:1F), which is in agreement with the current trend of the spread of the HIV/AIDS epidemic among women (12) .…”
Section: Discussionsupporting
confidence: 75%
See 4 more Smart Citations
“…The present study revealed a higher incidence of HIV among young adult males, as previously described by our group at the municipality of Catanduva, São Paulo (2) . However, there was a decrease in the male: female (M:F) ratio among infected individuals in the ART era (1.89M:1F), which is in agreement with the current trend of the spread of the HIV/AIDS epidemic among women (12) .…”
Section: Discussionsupporting
confidence: 75%
“…This result was also found by our group in a hospital in the City of Catanduva, located in a rural area of the State of São Paulo (2) . The growth of the epidemic in rural areas is reported in the Brazilian literature (18) .…”
Section: Discussionsupporting
confidence: 75%
See 3 more Smart Citations